(3TaGA UOhQ GdfGS TQM eYGfi GdCSGS dYbGFO GdCcjGS aj eYQaI QH GdYGdejf hYOdg aj GdeNdhbjfs - (3GdTQaj , CMeO Hf eMeO Hf UdGM Hf eMeO GdQGRj, TeS GdOjf,J (B1055 (3g` s
(3ChdgG (B:s
(3GdMeO dgd GdPi OdfG Ydi eYQaJg eeG CQfG ef YLGFH eUfhYGJg s
(3BNQgG (B:s
(3ajLH Cf jchf GdeQGO GdC(B'(3Xe YfO Gddg SHMGfg hJYGdi , hdjS cPdc Ci hdjS GdC(B'(3Xe YfO Gdgd ESJLH OYGA ehdGfG CejQ GdeDefjf GdefUhQ HGddg QH GdYGdejf GdbGSe Hf eMeO GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdgG ahGFO hfbhd hCbhGd heSGFd Ydi WQJgG hba ddeDdas
(3fSNI eUMMI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3CUhd Gdabgs